Magnetic properties of the self-doped lanthanum manganites La1-xMnO3 - Sankar, C. R.; Joy, Pattayil Alias (Physical Review B, 2005)
The magnetic properties of different compositions in the self-doped lanthanum manganites, La1-xMnO3, have been studied by ac susceptibility and dc magnetization measurements in the temperature range 10-300 K. All compositions with x < 0.125 show an anomalous decrease in the ac susceptibility and zero field cooled (ZFC) dc magnetization at low temperatures, below the ferromagnetic ordering temperature. The temperature below which this anomalous behavior is observed, T-a, varies with the degree of La vacancy in the series where the Mn4+ concentration decreases with increasing x. Moreover, T-a varies with the Mn4+ content for a given composition. However, in both cases, this temperature levels off when the concentration of Mn4+ is above 23%. The magnetic-transition-like feature broadens and shifts to further lower temperatures with increasing magnetic fields and vanishes when measured above a certain field. A small but drastic increase in the coercivity is observed below T-a. There is a direct correlation between the shapes of the curves of the inverse of the coercivity as a function of temperature and ac susceptibility, indicating the influence of magnetic anisotropy on the characteristics of the ac susceptibility and zero field cooled magnetization curves of the self-doped compounds. The direct correlation between the changes in the coercivity and ac susceptibility as well as ZFC magnetization when measured at low magnetic fields give evidence to the role of domain wall pinning effects, which varies with the degree of self-doping or Mn4+ concentration.